Enhanced Imaging Using Inverse Design of Nanophotonic Scintillators. Issue 8 (17th February 2023) - Shultzman, Avner; Segal, Ohad; Kurman, Yaniv; Roques‐Carmes, Charles; Kaminer, Ido
Abstract: Converting ionizing radiation into visible light is essential in a wide range of fundamental and industrial applications, such as electromagnetic calorimeters in high‐energy particle detectors, electron detectors, image intensifiers, and X‐ray imaging. These different areas of technology all rely on scintillators or phosphors, i.e., materials that emit light upon bombardment by high‐energy particles. In all cases, the emission is through spontaneous emission . The fundamental nature of spontaneous emission poses limitations on all these technologies, imposing an intrinsic trade‐off between efficiency and resolution in all imaging applications: thicker phosphors are more efficient due to their greater stopping power, which however comes at the expense of image blurring due to light spread inside the thicker phosphors. Here, the concept of inverse‐designed nanophotonic scintillators is proposed, which can overcome the trade‐off between resolution and efficiency by reshaping the intrinsic spontaneous emission. To exemplify the concept, multilayer phosphor nanostructures are designed and these nanostructures are compared to state‐of‐the‐art phosphor screens in image intensifiers, showing a threefold resolution enhancement simultaneous with a threefold efficiency enhancement. The enabling concept is applying the ubiquitous Purcell effect for the first time in a new context—for improving image resolution. Looking forward, this approach directly applies to a wide range of technologies, including X‐ray imaging applications. Abstract : Here, the concept of inverse‐designed nanophotonic scintillators is proposed, which can overcome the trade‐off between resolution and efficiency when converting ionizing radiation into visible light, by reshaping the intrinsic spontaneous emission. Looking forward, this approach directly applies to a wide range of technologies, including X‐ray imaging applications.